Paleolakes in the Northwest Hellas Region, Mars: Implications for the Regional Geologic History and Paleoclimate. Issue 3 (10th March 2020) - Zhao, Jiannan; Xiao, Long; Glotch, Timothy D.
Abstract: Hellas basin is one of the largest and oldest impact basins on the Martian surface. Its surrounding highland regions have undergone complicated geologic processes after the formation of Hellas basin. However, the geologic and climatic histories of the highlands surrounding Hellas are still unclear. Paleolakes provide us clues to answer these questions. In this study, we made a detailed investigation of paleolakes in the northwest Hellas region with high‐resolution imaging, topographic, and spectral data. A total of 64 paleolakes were identified with diameters larger than 4 km, in which 49 are newly reported. We calculated basic hydrologic parameters of the paleolakes and analyzed the sedimentary landforms, resurfacing processes, and aqueous minerals in the lake basins. Comprehensive analyses of the geomorphology, mineralogy, and age of the paleolakes revealed the geologic and climatic histories of the northwest Hellas region: a climate transition from warm and wet to semi‐arid happened in Noachian, and then lakes drained in a cold and dry climate in the early Hesperian, contemporary with or followed by a period of intense volcanic activity peaked around 3.3 Ga, and finally in the Amazonian, an extensive glacial event around 0.9 Ga resurfaced most of the paleolakes in the region south of 25°S. Our study also supports the existence of a "Hellas Ocean" and indicates that the Martian climate could have variations on regional scales and further studies are still needed to clarify the details. Plain Language Summary: Paleolake basins are widely distributed on the Martian surface and have attracted high attention as they record information on regional geologic history and climate change. Hellas basin is one of the largest and oldest impact basins on the Martian surface, and it has undergone complicated geologic processes associated with climate changes. In this paper, we studied the highland region around the northwest part of the Hellas basin. Detailed study of the paleolakes in this region could provide clues to reveal the geologic and climatic history. We identified 64 paleolakes with high‐resolution image and topographic data and analyzed their morphology, landforms, ages, and aqueous minerals. We found that the lakes drained around 3.6 billion years ago, contemporary with or followed by extensive volcanic activity peaked at ~3.3 billion years ago. Then, glacial activity happened in this area around 0.9 billion years ago. In addition, the distribution, morphology, and mineral composition of the paleolakes also indicate that the climate of the northwest Hellas region in Noachian may have undergone a transition from warm and wet to semi‐arid. Key Points: We identified 64 paleolakes in the northwest Hellas region and investigated their geomorphology, age, and mineralogy in detail Paleolakes drained in the early Hesperian and were extensively resurfaced by volcanic and glacial activity at ~3.3 and ~0.9 Ga, respectively A climate transition from warm and wet to semi‐arid then to cold and dry happened in the study region from the Noachian to the Hesperian